Potencial alelopático e composição fitoquímica do híbrido Eucalyptus urograndis - Souza, Maria Gabriela Marques de (2020)
The genus Eucalyptus has a high economic interest, due to its versatility regarding its use and the potential of its wood. Allelopathy exerted on other plants is one of the effects associated with eucalyptus monoculture. The hybrid Eucalyptus urograndis (